Association of Body Mass Index With Severity and Outcome of COVID-19 - Negar Javadinasab; Ozra Akha; Narges Mirzaei Ilali; Zohreh Rezaeian; Zahra Hosseini-khah (Research in Molecular Medicine)
Background: The COVID-19 pandemic, caused by SARS-CoV-2, has presented a global health challenge. Older people and patients with underlying conditions such as hypertension, diabetes, and obesity are more susceptible to severe disease outcomes. Obesity or high body mass (BMI) index is a significant risk factor for creating diabetes and plays a crucial role in the pathogenesis of COVID-19 infection. Obesity has been shown to increase vulnerability to infections, making it a significant risk factor for COVID-19. This study aims to investigate the relationship between BMI and COVID-19 severity and outcomes in patients with and without diabetes. Materials and Methods: This case-control study was conducted on 400 patients with confirmed COVID-19 infection, referred to teaching hospitals in Sari City, Iran, during April and May 2019. The study population consisted of 192 diabetic patients (case group) and 208 non-diabetic individuals (control group), matched for age and sex. Participants’ data, including demographics, medical history, laboratory findings, and disease progression details, were collected using a comprehensive questionnaire. According to CDC criteria, COVID-19 disease severity was defined as mild, moderate, and severe. The relationship between BMI and COVID-19 severity was compared between the diabetic and non-diabetic groups. Results: This study was conducted on 192 diabetic and 208 non-diabetic COVID-19 patients with an average age of 62.85±0.88 and 53.21±1.18 years, respectively. The average BMI in the diabetic group was 28.68±0.4, whereas it was 26.94±0.31 (P=0.001) in the non-diabetic group. There was a statistically significant difference in the severity of COVID-19 infection between diabetic and non-diabetic patients (P=0.008). The results showed a statistically significant difference in disease severity based on BMI in the diabetic group (P=0.02). Significant differences were observed in the need for mechanical ventilation (P=0.000) and mortality in people with diabetes compared to nondiabetics. A significant association was observed between BMI and ICU admission in both diabetic (P=0.001) and non-diabetic (P=0.000) groups. Conclusion: The study concluded that BMI may be a significant risk factor for severe COVID-19 outcomes, particularly among people with diabetes. This finding emphasizes the importance of BMI in disease prevention and control strategies, especially for populations with underlying conditions like diabetes.